Pemberdayaan Influencer Sebaya untuk Meningkatkan Literasi Kesehatan Remaja - Misrawati, Misrawati; Aminuddin, Al; Maesaroh, Siti; Tampubolon, Masrina Munawarah; Tampubolon, Nurhannifah Rizky (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Peer education has been widely used as a method of health education for adolescents. However, adolescent health problems are still a concern that requires adolescents to increase literacy and adopt a healthy lifestyle. Youth empowerment carried out in this activity is in the form of peer education using the term influencer to refer to peer educators. A total of 20 students who successfully passed the selection took part in training activities covering physical activity and fitness, reproductive health and nutrition in adolescents as well as using the uksku.id website as a medium for influencers to work. The results of data analysis using the T test showed p < 0.05, meaning there was a difference in knowledge before being given training and after being given training. Training carried out as a form of training for influencers can increase the influencer's knowledge to provide education to their peers. The influencers will then share their learning experiences and insights in the form of writing or posters which are then posted via the uksku.id website. It is hoped that this empowerment activity can become a new trend in increasing health literacy among students.